Tuberculin test errors and its effect on detection of bovine tuberculosis - BORHAM, M; OREIBY, A; EL-GEDAWY, A; HEGAZY, Y; AL-GAABARY, M (Journal of the Hellenic Veterinary Medical Society, 2022)
Bovine tuberculosis is an endemic disease in Egypt, a notable gap exists between limited cases identified by single intradermal tuberculin test performed through the national control program and higher detected cases at abattoirs. Therefore, this study aimed to investigate epidemiological situation and causes of the previously mentioned gap in Middle-Delta Region. A total of 25 emergency-slaughtered animals of unknown tuberculosis-status were investigated by cocktail-antigens ELISA and post-mortem examination. Five visible tuberculous-lesion cases were detected and confirmed by PCR, ELISA was sensitive and predictive of the existence of tuberculous-lesions; 4(80%) out of 5 visible-lesion cases were seropositive. True prevalence among the slaughtered animals was 27%. In addition, tuberculin-testing of 400 animals during the national control program was evaluated, many technical and procedural errors were detected, and all animals were negative.Out of them, 55 animals were tested by ELISA before the application of tuberculin test, 30 (54.5%) animals were seropositive. To confirm the effect of the reported errors on reliability of tuberculin test, reference serum of 20 tuberculosis-positive animals that were tested by standard-procedures tuberculin test and their status were confirmed by PCR after slaughtering, were tested by ELISA. A complete matching was evident, the 20 standard-tuberculin positive animals were all seropositive. In conclusion, bovine tuberculosis is endemic at high levels in the study area, reported errors of tuberculin test during national control program may be the cause for missing tuberculosis cases and not tuberculin test itself and finally, a further wide-scale funded study is required to discover the situation throughout Egypt.